Use of Porcine Factor VIII in the Management of Seventeen Patients with Factor VIII Antibodies - Gatti, Loredana; Mannucci, Pier Mannuccio (Thrombosis and Haemostasis, 1984)
A polyelectrolyte-fractionated porcine factor VIII concentrate was given to 16 hemophiliacs with anti-F VIII antibodies (Ab) and to a woman with post-partum-acquired Ab during 24 courses of treatment including three major surgical procedures. Before treatment, antiporcine F VIII Ab was always lower than antihuman F VIII Ab, with a median cross reactivity of 32%. After treatment, the mean rise in F VIII was 1.5 U/dl/Unit infused/Kg b.w. and in vivo recovery was 50% of the theoretical values. Anamnestic rises in anti-porcine F VIII Ab (3 × the baseline titer) were seen after 9 of 22 courses of treatment with porcine F VIII only; similar rises in anti-human F VIII Ab, after 6 courses of treatment; median cross reactivity did not change significantly. Lower than expected increases in plasma F VIII without marked changes in Ab titers and severe thrombocytopenia occurred during surgery in two patients. Porcine F VIII is a rational and effective therapeutic choice for patients who have anti-human Ab titers above 10 U/ml; it can solve clinical situations that would otherwise be very difficult to manage; anamnesis is perhaps less frequent than after human F VIII; however, the incidence of thrombocytopenia, resistance and other side- effects is still higher than desirable.
Keywords: Factor VIII; Polyelectrolyte; Factor VIII antibodies; Hemophilia therapy